2020
DOI: 10.1002/aenm.201902795
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐State Prelithiation Enables High‐Performance Li‐Al‐H Anode for Solid‐State Batteries

Abstract: Lithium alanates exhibit high theoretical specific capacities and appropriate lithiation/delithiation potentials, but suffer from poor reversibility, cycling stability, and rate capability due to their sluggish kinetics and extensive side reactions. Herein, a novel and facile solid‐state prelithiation approach is proposed to in situ prepare a Li3AlH6‐Al nanocomposite from a short‐circuited electrochemical reaction between LiAlH4 and Li with the help of fast electron and Li‐ion conductors (C and P63mc LiBH4). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 46 publications
0
35
0
Order By: Relevance
“…During charge process, Li is first fully delithiated to Al. The big adventage is that during cycling the morphological structure is well maintaned, thus resulting in cyclig stability of electrode [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During charge process, Li is first fully delithiated to Al. The big adventage is that during cycling the morphological structure is well maintaned, thus resulting in cyclig stability of electrode [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…In work [ 48 ], the authors synthesized Li 3 AlH 6 -Al nanocomposite and obtained a high specific capacity (2266 mAh g −1 ), Coulombic efficiency (88%), cycling stability (71% retention in the 100th cycle), and rate capability (1429 mAh g −1 at 1 A g −1 ) as a anode in LIBs. It was also shown that, during the intercalation process, reactions given by Equations (5) and (6) could be applied: …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To accommodate high-voltage cathodes, such as commercial LiCoO 2 , suldes have recently been introduced to decrease the interfacial resistance between LiCoO 2 and hydride-based SSEs by forming a stable Li-ion conductive cathode electrolyte interphase (CEI) layer. 135,140 These hydride-based CSSEs can work well in allsolid-state LIBs with a LiCoO 2 cathode, which exhibits typical high-voltage plateaus for charge/discharge.…”
Section: Hydride-based Cssesmentioning
confidence: 99%
“…However, uncontrollable dendrite formation, large volume expansion during the lithium deposition and the unstable SEI have caused serious safety problems and rapid capacity fading of the lithium metal batteries (Lin et al, 2017b), which have restricted the application of lithium metal anode. Researchers have proposed some methods to solve these problems such as designing a three-dimensional (3D) current collector to induce uniform lithium deposition and mitigate the volume change of the lithium anode (Yun et al, 2016), constructing coating layer on separator to control lithium dendrite growth (Liu Y. et al, 2017), improving the stability and mechanical strength of the SEI on the surface of lithium anode to inhibit the growth of dendrites (Gao et al, 2019), and employing non-flammable solid electrolyte to block Li dendrites and mitigating the safety hazards (Lu et al, 2019;Zhu et al, 2019;Pang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%